Retracted: Magnesium protects mouse hippocampal HT22 cells against hypoxia‐induced injury by upregulation of miR‐221. Issue 2 (12th September 2019) - Mi, Fuli; Liu, Fuyu; Zhang, Chuanzhu
Abstract: Magnesium (Mg 2+ ) has been shown to exert neuroprotective effects against hypoxia. However, it still remains elusive whether Mg 2+ protected mouse hippocampal HT22 cells against hypoxia‐evoked damages. Therefore, we aimed to investigate the function of Mg 2+ and mechanisms associated with microRNA‐221 (miR‐221). HT22 cells were exposed to 3% O2 for 24 hours to induce hypoxic damages with 21% as a normoxic culture condition. The damages were monitored by viability, migration, and apoptosis of HT22 cells with or without Mg 2+ pretreatment. Quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) was applied to examine the alteration of miR‐221, miR‐210, and miR‐17‐5p. Transduction was carried out to artificially alter the expression of miR‐221 and nerve growth factor (NGF), which was confirmed by qRT‐PCR or Western blot assays. To blunt phosphoinositide 3‐kinase (PI3K)/protein kinase B (AKT) and nuclear factor κB (NF‐κB), LY294002 (10 µM) and BAY 11‐7082 (10 µM) were used. We observed Mg 2+ protected HT22 cells against hypoxia‐induced damages by upregulating miR‐221. Further, miR‐221 positively regulated NGF expression. Overexpression of NGF alleviated cell injury, while suppression of NGF aggravated cell injury. Moreover, miR‐221 elevated NGF by inducing phosphorylation of regulators in PI3K/AKT and NF‐κB transduction cascades and then alleviated cell injury. In conclusion, Mg 2+ protected HT22 cells against hypoxia‐induced damages by upregulation of miR‐221 and NGF. These findings provided insights into the development of improved strategies for clinical application. Abstract : Magnesium protects against hypoxia‐evoked lesions through upregulation of microRNA‐221 and nerve growth factor in mouse HT22 hippocampal cells. These findings provide insights into the development of improved strategies for clinical application.